Laminate and roll
By introducing fluoropolymer and woven fabric into the solid polymer electrolyte membrane and forming good adhesion between the release layer and the film, the problem of poor rolling out properties when rolling out of the laminated body is solved, and excellent rolling out properties and adhesion are achieved.
Patent Information
- Application Number
- CN202380054433.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-07-12
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, when the laminated body including a peelable base material and a solid polymer electrolyte film is rolled out in the roll, the laminated body cannot be rolled out stably, resulting in poor rolling out performance.
By introducing a fluoropolymer with ion exchange groups into the solid polymer electrolyte membrane, and forming a good adhesion between the release layer and the solid polymer electrolyte membrane, it is wound by winding itself to form a roll body, ensuring that the rolled roll body has excellent rolling properties.
Excellent adhesion between the release layer and the solid polymer electrolyte membrane and excellent rolling out properties of the rolling body are achieved, ensuring the effect of stably rolling out the laminated body in the rolling body.
Smart Images

Figure CN119605003A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate and a roll. Background Art
[0002] Solid polymer electrolyte membranes are used in various applications and various studies have been conducted. For example, solid polymer electrolyte membranes are used in membrane electrode assemblies.
[0003] A solid polymer electrolyte membrane is laminated with various films on its surface depending on the application. For example, when a solid polymer electrolyte membrane is applied to a membrane electrode assembly, an electrode membrane (catalyst layer or electrode catalyst layer) is laminated on the surface of the solid polymer electrolyte membrane, and this electrode membrane is sometimes formed by a casting method or a coating method.
[0004] For example, Patent Document 1 (paragraph 0051) discloses a technique in which a catalyst is applied to the surface of an electrolyte sheet in a state where the electrolyte sheet is attached to a polyethylene terephthalate back sheet via a release layer.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-107430 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] When using a releasable substrate comprising a support such as polyethylene terephthalate and a release layer as described in Patent Document 1, good adhesion between the release layer and the solid polymer electrolyte membrane is required to prevent the solid polymer electrolyte membrane disposed on the release layer from peeling off during handling.
[0010] In addition, a laminate including a releasable substrate and a solid polymer electrolyte membrane is often wound and transported in the form of a roll, and the laminate is often unwound from the roll and used.
[0011] The present inventors have found that the laminate cannot be stably unrolled from the roll of the laminate comprising a peelable substrate and a solid polymer electrolyte membrane described in Patent Document 1. It should be noted that the ability to stably unroll a film from a roll is hereinafter referred to as "excellent unrolling property".
[0012] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a laminate having excellent adhesion between a release layer and a solid polymer electrolyte membrane and excellent unwinding properties from a roll obtained by winding.
[0013] Another object of the present invention is to provide a roll.
[0014] Solutions for solving problems
[0015] The present inventors have conducted intensive studies on the above-mentioned problems and have found that the above-mentioned problems can be solved by the following technical solutions.
[0016] (1) A laminate comprising a releasable substrate and a solid polymer electrolyte membrane, wherein the releasable substrate comprises a support and a release layer, and the solid polymer electrolyte membrane is disposed on the release layer in the releasable substrate,
[0017] The solid polymer electrolyte membrane comprises a fluorine-containing polymer having ion exchange groups and a woven fabric.
[0018] (2) The laminate according to (1), wherein the ion exchange capacity of the fluorinated polymer is 0.90 to 2.00 milliequivalents / g of dry resin.
[0019] (3) The laminate according to (1) or (2), wherein the woven fabric is composed of yarns A extending in one direction and yarns B extending in a direction substantially orthogonal to the yarns A,
[0020] The opening ratio of the woven fabric is 50% or more.
[0021] (4) The laminate according to (3), wherein the denier of the yarn A and the denier of the yarn B are each independently 15 to 50.
[0022] (5) The laminate according to (3) or (4), wherein the yarns A and B are each independently composed of at least one material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyetheretherketone and polyphenylene sulfide.
[0023] (6) The laminate according to any one of (3) to (5), wherein the density of the yarns A and B is independently 70 to 150 yarns / inch.
[0024] (7) The laminate according to any one of (1) to (6), wherein the ion exchange group is a sulfonic acid type functional group.
[0025] (8) The laminate according to any one of (1) to (7), wherein the fluorinated polymer comprises a unit based on a fluorinated olefin and a unit having a sulfonic acid type functional group and a fluorine atom.
[0026] (9) The laminate according to (8), wherein the fluorine-containing olefin is a fluorine olefin having one or more fluorine atoms in a molecule and having 2 to 3 carbon atoms.
[0027] (10) The laminate according to (8) or (9), wherein the unit having a sulfonic acid type functional group and a fluorine atom is a unit represented by the formula (1) described below.
[0028] (11) The laminate according to any one of (1) to (10), wherein the elastic modulus of the support at 160°C is larger than the elastic modulus of the release layer at 160°C.
[0029] (12) The laminate according to any one of (1) to (11), wherein the elastic modulus of the release layer at 160° C. is 1 MPa or less.
[0030] (13) The laminate according to any one of (1) to (12), wherein the woven fabric is composed of yarns A extending in one direction and yarns B extending in a direction substantially orthogonal to the yarns A,
[0031] The maximum film thickness TA and the minimum film thickness TB of the solid polymer electrolyte membrane were measured at 10 different cross sections when the solid polymer electrolyte membrane was cut in a direction parallel to the extension direction of the aforementioned filaments A in the solid polymer electrolyte membrane and at the midpoint between the filaments A.
[0032] Furthermore, the maximum film thickness TA and the minimum film thickness TB of the solid polymer electrolyte membrane were measured at 10 different cross sections when the solid polymer electrolyte membrane was cut in a direction parallel to the extension direction of the filaments B in the solid polymer electrolyte membrane and at the midpoint between the filaments B.
[0033] The average minimum film thickness obtained by arithmetic averaging the 20 TBs obtained is set as TB. AVE , and the average maximum film thickness obtained by arithmetic averaging the 20 TAs obtained is set as TA AVE When the average maximum film thickness TA AVE and the average minimum film thickness TB AVE The relationship of the following formula (X) is satisfied.
[0034] (14) A roll obtained by winding the laminated body according to any one of (1) to (13).
[0035] Effects of the Invention
[0036] According to the present invention, it is possible to provide a laminate having excellent adhesion between the release layer and the solid polymer electrolyte membrane and excellent unwinding properties from a roll obtained by winding.
[0037] Furthermore, according to the present invention, a roll body can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1This is a cross-sectional view showing an example of the laminated body of the present invention.
[0039] Figure 2 It is a cross-sectional view showing another example of the laminated body of the present invention.
[0040] Figure 3 This is a cross-sectional view showing an example in which the solid polymer electrolyte membrane is cut in a direction parallel to the direction in which the yarn A extends.
[0041] Figure 4 This is a cross-sectional view showing an example in which the solid polymer electrolyte membrane is cut in a direction parallel to the direction in which the wire B extends.
[0042] Figure 5 It is a schematic plan view showing an example of a woven fabric included in a solid polymer electrolyte membrane when viewed in the membrane thickness direction of the solid polymer electrolyte membrane. DETAILED DESCRIPTION
[0043] The definitions of the following terms apply to this specification and claims unless otherwise specified.
[0044] The "ion exchange group" refers to a group that can replace at least a part of ions contained in the group with other ions, and examples thereof include the following sulfonic acid type functional group and carboxylic acid type functional group.
[0045] "Sulfonic acid functional group" refers to a sulfonic acid group (-SO3H) or a sulfonate group (-SO3M 2 Among them, M 2 is an alkali metal or a quaternary ammonium cation. ).
[0046] "Carboxylic acid-type functional group" refers to a carboxylic acid group (-COOH) or a carboxylate group (-COOM 1 Among them, M 1 is an alkali metal or a quaternary ammonium cation. ).
[0047] "Precursor membrane" refers to a membrane comprising a polymer having groups that can be converted into ion exchange groups.
[0048] The "group that can be converted into an ion exchange group" means a group that can be converted into an ion exchange group by a treatment such as a hydrolysis treatment or an acidification treatment.
[0049] The "group that can be converted into a sulfonic acid type functional group" means a group that can be converted into a sulfonic acid type functional group by a treatment such as a hydrolysis treatment or an acidification treatment.
[0050] The "unit" in a polymer refers to an atomic group derived from one molecule of a monomer and formed by polymerizing the monomer. The unit may be an atomic group directly formed by a polymerization reaction, or may be an atomic group in which a part of the atomic group is converted into an atomic group of another structure by treating the polymer obtained by the polymerization reaction.
[0051] A numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0052] [Laminated body]
[0053] The laminate of the present invention comprises a peelable substrate and a solid polymer electrolyte membrane, wherein the peelable substrate comprises a support and a release layer, the solid polymer electrolyte membrane is arranged on the release layer in the peelable substrate, and the solid polymer electrolyte membrane comprises a fluorine-containing polymer having ion exchange groups and a woven fabric.
[0054] The laminate of the present invention has excellent adhesion between the release layer and the solid polymer electrolyte membrane and excellent unwinding properties when the laminate is unwound from a roll obtained by winding the laminate. The detailed reason is not clear, but it is presumed to be the following reason.
[0055] The solid polymer electrolyte membrane in the laminate of the present invention includes a woven fabric. Due to the presence of the woven fabric, a micro-concave-convex structure is formed on the surface of the solid polymer electrolyte membrane. It can be inferred that by providing the surface of the release layer side of the solid polymer electrolyte membrane with such a concave-convex structure, the material of the release layer enters into the concave part of the concave-convex structure of the surface of the release layer side of the solid polymer electrolyte membrane, etc., generating an anchoring effect, and as a result, the adhesion of the two is improved.
[0056] In addition, since the concavo-convex structure exists on the surface of the side opposite to the release layer side of the solid polymer electrolyte membrane, when the laminate is wound to form a roll, the concavo-convex structure contacts the surface of the support side of the peelable substrate. It is speculated that the presence of such a concavo-convex structure suppresses so-called sticking, and when the laminate is unrolled, the laminate can be unrolled stably.
[0057] It is also presumed that even if the surface of the support on the side opposite to the release layer side in the releasable substrate is subjected to pear-finishing treatment, when the laminate is unrolled in the same manner, the laminate can be stably unrolled.
[0058] It is also speculated that if the laminate is a laminate in which a fluorine-based film or a polyethylene film having excellent mold release properties is attached to the surface of the support body on the side opposite to the release layer side in the peelable substrate, the above-mentioned blocking can be suppressed, and the laminate can be more stably unrolled when the laminate is unrolled. It is further speculated that even if the surface of the attached fluorine-based film or polyethylene film on the side opposite to the peelable substrate side is pear-grounded, the laminate can be stably unrolled when the laminate is unrolled in the same manner as described above.
[0059] Figure 1 1 is a cross-sectional view showing an example of a laminate of the present invention. The laminate 10 includes a releasable substrate 12 and a solid polymer electrolyte membrane 14, and the releasable substrate 12 includes a support 16 and a release layer 18. In the releasable substrate 12, the release layer 18 is arranged on the solid polymer electrolyte membrane 14 side, and the solid polymer electrolyte membrane 14 is arranged on the release layer 18 in a manner of contacting the release layer 18.
[0060] Hereinafter, each member in the stacked body will be described in detail.
[0061] [Releasable substrate]
[0062] The peelable substrate is a substrate that supports the solid polymer electrolyte membrane and is peeled off.
[0063] The releasable substrate includes a support and a release layer.
[0064] Hereinafter, each member included in the releasable substrate will be described in detail.
[0065] (Supporting body)
[0066] The support body is a member for supporting the release layer.
[0067] Specific examples of the support include a resin plate, a glass plate, and a metal plate.
[0068] When the support is a resin plate, the material contained in the support includes, for example, polyester, polyolefin, polyamide, polyimide, polycarbonate, polyphenylene ether, polyphenylene sulfide, cellulose derivatives and the like. Among them, polyester or polyimide is preferred, and polyester is more preferred from the viewpoint of heat resistance and flexibility.
[0069] Examples of the polyester include polyethylene terephthalate and polyethylene naphthalate.
[0070] When the support is a resin plate, the content of the resin in the support is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, with an upper limit of 100% by mass, based on the total mass of the support.
[0071] The thickness of the support is preferably 5 to 188 μm, more preferably 25 to 100 μm. When the thickness of the support is within the above range, the balance between handling properties and thickness reduction is excellent, and the support can be suitably applied to a roll-to-roll method involving a heat treatment.
[0072] The thickness of the support body is an average thickness, which is a value obtained by measuring the thicknesses at five or more arbitrary locations of the support body and calculating the arithmetic average of the thicknesses.
[0073] The elastic modulus of the support at 160° C. is preferably 5 to 100 MPa, more preferably 20 to 60 MPa. When the thickness of the support is within the above range, the balance between dimensional stability and thickness reduction is excellent, and the support can be suitably applied to a roll-to-roll method involving a heat treatment.
[0074] The elastic modulus of the support can be measured by a method based on JIS K7161.
[0075] (Release layer)
[0076] The release layer is a layer disposed in contact with a solid polymer electrolyte membrane described later.
[0077] Examples of the material contained in the release layer include resins such as polyolefins, and polyethylene and polypropylene are particularly preferred from the viewpoint of excellent balance between adhesion to the solid polymer electrolyte membrane and releasability.
[0078] The weight average molecular weight of the polyethylene is preferably 20,000 to 7,000,000, more preferably 20,000 to 300,000.
[0079] The weight average molecular weight of the polypropylene is preferably 40,000 to 300,000, more preferably 40,000 to 200,000.
[0080] When the release layer contains a resin, the content of the resin in the release layer is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more, based on the total mass of the release layer. The upper limit is 100% by mass.
[0081] The thickness of the release layer is preferably 5 to 200 μm, more preferably 25 to 100 μm. When the thickness of the release layer is within the above range, the balance between adhesion to the solid polymer electrolyte membrane and thickness reduction is excellent.
[0082] The thickness of the release layer is an average thickness, which is a value obtained by measuring the thickness at five or more arbitrary locations of the release layer and taking the arithmetic average of the thicknesses.
[0083] The elastic modulus of the release layer at 160° C. is preferably 1 MPa or less, more preferably 0.5 MPa or less. The lower limit of the elastic modulus is not particularly limited. In this specification, when a test piece for measuring the elastic modulus is clamped by a clamp of a tensile tester under an environment of 160° C., if the test piece melts and falls off and cannot be measured itself, the elastic modulus is expressed as 0 MPa.
[0084] The elastic modulus of the support at 160° C. is preferably greater than the elastic modulus of the release layer at 160° C. For example, the elastic modulus of the support at 160° C. is more preferably 1 to 80 MPa greater than the elastic modulus of the release layer at 160° C., and further preferably 5 to 50 MPa greater. When the elastic modulus of the support at 160° C. is greater than the elastic modulus of the release layer at 160° C., when the laminate is applied in a roll-to-roll method accompanied by a heat treatment, the dimensional stability of the laminate is excellent.
[0085] The method for measuring the elastic modulus of the release layer is the same as the method for measuring the elastic modulus of the support.
[0086] (Other layers)
[0087] The releasable substrate may include other layers in addition to the support and the release layer. For example, the releasable substrate may include an adhesion layer between the support and the release layer for improving the adhesion between the two.
[0088] Examples of the adhesion layer include an adhesion layer obtained using an adhesive and an adhesion layer obtained using a pressure-sensitive adhesive.
[0089] (Method for producing a releasable substrate)
[0090] As a method for producing a releasable substrate, for example, the following method can be cited: a release layer-forming composition containing a resin and a solvent capable of forming a release layer is applied to a support, and a drying treatment and a curing treatment are performed as needed to form a release layer. In addition, a method of applying a molten resin to a support to form a release layer can also be cited. In addition, a dry lamination method of applying an adhesive solution to a support, drying it, and then further attaching a release layer can also be cited.
[0091] [Solid polymer electrolyte membrane]
[0092] The solid polymer electrolyte membrane comprises a fluorine-containing polymer having an ion exchange group (hereinafter also referred to as "fluorine-containing polymer (I)") and a woven fabric.
[0093] Hereinafter, first, the materials included in the polymer electrolyte membrane will be described in detail, and then the characteristics of the solid polymer electrolyte membrane will be described in detail.
[0094] (Fluoropolymer (I))
[0095] From the viewpoint of being able to further reduce the electrolysis voltage when the solid polymer electrolyte membrane is applied to a membrane electrode assembly, the ion exchange capacity of the fluoropolymer (I) is preferably 0.90 milliequivalent / g dry resin or more, more preferably greater than 1.10 milliequivalent / g dry resin, further preferably 1.15 milliequivalent / g dry resin or more, particularly preferably 1.20 milliequivalent / g dry resin or more, and most preferably 1.25 milliequivalent / g dry resin or more.
[0096] From the viewpoint of obtaining more excellent properties of the solid polymer electrolyte membrane, the upper limit of the ion exchange capacity of the fluoropolymer (I) is preferably 2.00 milliequivalents / g dry resin or less, more preferably 1.50 milliequivalents / g dry resin or less, and still more preferably 1.43 milliequivalents / g dry resin or less.
[0097] The fluorinated polymer (I) used in the solid polymer electrolyte membrane may be one kind or two or more kinds thereof may be laminated or mixed and used.
[0098] The solid polymer electrolyte membrane may contain polymers other than the fluorinated polymer (I) (hereinafter also referred to as "other polymers"), and the polymer in the solid polymer electrolyte membrane is preferably substantially composed of the fluorinated polymer (I). Substantially composed of the fluorinated polymer (I) means that the content of the fluorinated polymer (I) is 95% by mass or more relative to the total mass of the polymer in the solid polymer electrolyte membrane. As the upper limit of the content of the fluorinated polymer (I), 100% by mass can be cited relative to the total mass of the polymer in the solid polymer electrolyte membrane.
[0099] Specific examples of other polymers include one or more polyazole compounds selected from the group consisting of polymers of heterocyclic compounds containing one or more nitrogen atoms in the ring and polymers of heterocyclic compounds containing one or more nitrogen atoms in the ring and oxygen and / or sulfur atoms.
[0100] Specific examples of the polyazole compound include polyimidazole compounds, polybenzimidazole compounds, polybenzbisimidazole compounds, polybenzoxazole compounds, polyoxazole compounds, polythiazole compounds, and polybenzothiazole compounds.
[0101] In addition, from the viewpoint of oxidation resistance of the solid polymer electrolyte membrane, other polymers include polyphenylene sulfide resin and polyphenylene ether resin.
[0102] The fluorinated polymer (I) has an ion exchange group. Specific examples of the ion exchange group include sulfonic acid functional groups and carboxylic acid functional groups. Sulfonic acid functional groups are preferred from the viewpoint of further reducing the electrolysis voltage when the solid polymer electrolyte membrane is applied to a membrane electrode assembly.
[0103] Hereinafter, an embodiment of the fluorinated polymer having a sulfonic acid type functional group (hereinafter also referred to as “fluorinated polymer (S)”) will be described in detail.
[0104] The fluorinated polymer (S) preferably contains a unit based on a fluorinated olefin and a unit having a sulfonic acid type functional group and a fluorine atom.
[0105] Examples of the fluorinated olefin include fluorinated olefins having 2 to 3 carbon atoms and having one or more fluorine atoms in the molecule. Specific examples of the fluorinated olefin include tetrafluoroethylene (hereinafter also referred to as "TFE"), chlorotrifluoroethylene, vinylidene fluoride, vinyl fluoride, and hexafluoropropylene. Among them, TFE is preferred from the viewpoint of the production cost of the monomer, the reactivity with other monomers, and the excellent properties of the obtained fluorinated polymer (S).
[0106] The fluorinated olefins may be used alone or in combination of two or more.
[0107] As the unit having a sulfonic acid type functional group and a fluorine atom, a unit represented by formula (1) is preferred.
[0108] Formula (1) -[CF2-CF(-L-(SO3M) n )]-
[0109] L is an n+1-valent perfluorocarbon group which may contain an etheric oxygen atom.
[0110] The etheric oxygen atom may be located at the terminal of the perfluorocarbon group or between carbon atoms.
[0111] In the n+1-valent perfluorocarbon group, the number of carbon atoms is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0112] L is preferably an n+1-valent perfluoroaliphatic hydrocarbon group optionally containing an etheric oxygen atom, and more preferably n=1, i.e. a divalent perfluoroalkylene group optionally containing an etheric oxygen atom, or n=2, i.e. a trivalent perfluoroaliphatic hydrocarbon group optionally containing an etheric oxygen atom.
[0113] The divalent perfluoroalkylene group may be either linear or branched.
[0114] M is a hydrogen atom, an alkali metal or a quaternary ammonium cation.
[0115] n is 1 or 2. When n is 2, a plurality of M's may be the same or different.
[0116] The unit represented by formula (1) is preferably a unit represented by formula (1-1), a unit represented by formula (1-2), a unit represented by formula (1-3), or a unit represented by formula (1-4).
[0117] Formula (1-1) -[CF2-CF(-OR f1 -SO3M)]-
[0118] Formula (1-2) -[CF2-CF(-R f1 -SO3M)]-
[0119]
[0120]
[0121] R f1 The perfluoroalkylene group is a perfluoroalkylene group which may contain an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0122] R f2 The perfluoroalkylene group is a single bond or optionally contains an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0123] R f3 The perfluoroalkylene group is a single bond or optionally contains an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0124] r is 0 or 1.
[0125] m is 0 or 1.
[0126] M is a hydrogen atom, an alkali metal or a quaternary ammonium cation.
[0127] As the unit represented by the formula (1-1) and the unit represented by the formula (1-2), the unit represented by the formula (1-5) is preferred.
[0128] Formula (1-5) -[CF2-CF(-(CF2) x -(OCF2CFY) y -O-(CF2) z -SO3M)] -x is 0 or 1, y is an integer of 0 to 2, z is an integer of 1 to 4, and Y is F or CF3. M is as described above.
[0129] Specific examples of the unit represented by formula (1-1) include the following units: w in the formula is an integer of 1 to 8, and x is an integer of 1 to 5. M in the formula has the same meaning as described above.
[0130] -[CF2-CF(-O-(CF2)w -SO3M)]-
[0131] -[CF2-CF(-O-CF2CF(CF3)-O-(CF2) w -SO3M)]-
[0132] -[CF2-CF(-(O-CF2CF(CF3)) x -SO3M)]-
[0133] Specific examples of the unit represented by formula (1-2) include the following units: w in the formula is an integer of 1 to 8. M in the formula has the same meaning as described above.
[0134] -[CF2-CF(-(CF2) w -SO3M)]-
[0135] -[CF2-CF(-CF2-O-(CF2) w -SO3M)]-
[0136] The unit represented by the formula (1-3) is preferably a unit represented by the formula (1-3-1). M in the formula has the same meaning as described above.
[0137]
[0138] R f4 is a linear perfluoroalkylene group having 1 to 6 carbon atoms, R f5 It is a single bond or a linear perfluoroalkylene group which may contain an oxygen atom between carbon atoms and has 1 to 6 carbon atoms. r and M are as defined above.
[0139] Specific examples of the unit represented by formula (1-3-1) include the following.
[0140]
[0141] The unit represented by formula (1-4) is preferably a unit represented by formula (1-4-1). f1 , R f2 and M are defined as above.
[0142]
[0143] Specific examples of the unit represented by formula (1-4-1) include the following.
[0144]
[0145] The unit having a sulfonic acid type functional group and a fluorine atom may be used alone or in combination of two or more.
[0146] The fluorine-containing polymer (S) may contain units based on monomers other than the units based on the fluorine-containing olefin and the units having a sulfonic acid type functional group and a fluorine atom (hereinafter also referred to as "other monomers").
[0147] Specific examples of other monomers include CF2=CFR f6 (Among them, R f6 is a perfluoroalkyl group having 2 to 10 carbon atoms), CF2=CF-OR f7 (Among them, R f7 is a perfluoroalkyl group having 1 to 10 carbon atoms), CF2=CFO(CF2) v CF=CF2 (wherein v is an integer from 1 to 3).
[0148] From the viewpoint of maintaining the ion exchange performance, the content of the units based on other monomers is preferably at most 30 mass % based on all the units in the fluorinated polymer (S).
[0149] (Weaving)
[0150] From the viewpoint of further reducing the electrolysis voltage when the solid polymer electrolyte membrane is applied to a membrane electrode assembly, the opening ratio of the woven fabric is preferably 50.0% or more, more preferably 55.0% or more, further preferably 60.0% or more, particularly preferably 70.0% or more.
[0151] From the viewpoint of achieving better strength of the solid polymer electrolyte membrane, the upper limit of the opening ratio of the woven fabric is preferably 90.0% or less, more preferably 80.0% or less.
[0152] The open area ratio of the woven fabric is calculated by the following formula (ε) from the average diameter R1 of the filaments and the average interval P1 between adjacent filaments (hereinafter also referred to as “pitch P1”).
[0153] Here, the average diameter R1 of the filaments refers to the arithmetic mean of the diameters of 10 different filaments selected at random based on the magnified image (e.g., 100 times) of the woven surface obtained using a microscope. In addition, the spacing P1 refers to the arithmetic mean of 10 points at intervals of arbitrarily selected different parts based on the magnified image (e.g., 100 times) of the woven surface obtained using a microscope.
[0154] Opening ratio of fabric (%) = [P1 / (P1+R1)] 2 ×100(ε)
[0155] From the viewpoint of achieving better strength and dimensional stability of the solid polymer electrolyte membrane, the denier of the yarn A and the denier of the yarn B constituting the woven fabric are each independently preferably 2.0 or more, more preferably 10.0 or more, and even more preferably 15.0 or more.
[0156] From the viewpoint of being able to further reduce the electrolysis voltage when applying the solid polymer electrolyte membrane to the membrane electrode assembly, the upper limits of the denier of yarn A and the denier of yarn B constituting the woven fabric are each independently preferably less than 60.0, more preferably less than 50.0, and further preferably less than 20.0.
[0157] In addition, the denier is a value obtained by expressing the mass of 9000 m of yarn in grams (g / 9000 m).
[0158] From the viewpoint of excellent strength and dimensional stability of the solid polymer electrolyte membrane, the density of filaments A and B is preferably 50 strands / inch (19.7 strands / cm) or more, more preferably 70 strands / inch (27.6 strands / cm) or more, and further preferably 90 strands / inch (35.4 strands / cm) or more, and from the viewpoint of being able to further reduce the electrolysis voltage when the solid polymer electrolyte membrane is applied to a membrane electrode assembly, it is preferably 200 strands / inch (78.7 strands / cm) or less, more preferably 150 strands / inch (59.1 strands / cm) or less, and further preferably 100 strands / inch (39.4 strands / cm) or less.
[0159] The yarn A and the yarn B may be composed of either a monofilament composed of one filament or a multifilament composed of two or more filaments, and are preferably monofilaments.
[0160] From the viewpoint of better durability of the yarn, yarn A and yarn B are each independently preferably composed of at least one material selected from the group consisting of polytetrafluoroethylene (hereinafter also referred to as "PTFE"), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (hereinafter also referred to as "PFA"), polyetheretherketone (hereinafter also referred to as "PEEK") and polyphenylene sulfide (hereinafter also referred to as "PPS").
[0161] From the viewpoint of achieving better durability and strength of the yarn, the yarn A and the yarn B are preferably composed of slit yarns.
[0162] In the woven fabric, the yarns A and B are preferably substantially orthogonal. Substantially orthogonal means that the angle formed by the yarns A and B is 90±10 degrees.
[0163] The yarn A may be a warp yarn or a weft yarn of a woven fabric. When the yarn A is a weft yarn, the yarn B is a warp yarn. When the yarn A is a warp yarn, the yarn B is a weft yarn.
[0164] When the material constituting the woven fabric is PTFE, the weight per unit area of the woven fabric is preferably 20.0 to 40.0 g / m2 from the viewpoint of achieving an excellent balance between the strength and the handling properties of the solid polymer electrolyte membrane. 2 , more preferably 30.0 to 40.0 g / m 2 .
[0165] When the material constituting the woven fabric is PFA, the weight per unit area of the woven fabric is preferably 10.0 to 30.0 g / m2 from the viewpoint of achieving an excellent balance between the strength and the handling properties of the solid polymer electrolyte membrane. 2 , more preferably 10.0 to 20.0 g / m 2 .
[0166] When the material constituting the woven fabric is PEEK, the weight per unit area of the woven fabric is preferably 5.0 to 40.0 g / m2 from the viewpoint of excellent balance between the strength and the handling properties of the solid polymer electrolyte membrane. 2 , more preferably 5.0 to 30.0 g / m 2 .
[0167] When the material constituting the woven fabric is PPS, the weight per unit area of the woven fabric is preferably 5.0 to 40.0 g / m2 from the viewpoint of achieving an excellent balance between the strength and the handling properties of the solid polymer electrolyte membrane. 2 , more preferably 5.0 to 30.0 g / m 2 .
[0168] (Characteristics of solid polymer electrolyte membrane)
[0169] The solid polymer electrolyte membrane may have a single-layer structure or a multi-layer structure, but is preferably a single-layer structure.
[0170] In the case of a multilayer structure, for example, a configuration in which a plurality of layers containing a fluorinated polymer (I) and having mutually different ion exchange capacities are stacked may be mentioned.
[0171] The surface of the release layer side of the solid polymer electrolyte membrane preferably has a concavo-convex structure. By making the surface of the release layer side of the solid polymer electrolyte membrane have a concavo-convex structure, the material of the release layer enters the concave part of the above-mentioned concavo-convex structure, and as a result, the adhesion between the solid polymer electrolyte membrane and the release layer is improved.
[0172] The above-mentioned concavo-convex structure is formed by including a woven fabric in the solid polymer electrolyte membrane. For example, by adjusting the film thickness of the solid polymer electrolyte membrane, the height of the convex parts of the concavo-convex structure can be adjusted.
[0173] The surface of the solid polymer electrolyte membrane on the side opposite to the release layer side preferably has a concavo-convex structure. By making the surface of the solid polymer electrolyte membrane on the side opposite to the release layer side have a concavo-convex structure, when the laminate is wound into a roll, the surface of the solid polymer electrolyte membrane on the side opposite to the release layer side and the surface of the peelable substrate on the side opposite to the release layer side are easy to slide, and as a result, when the laminate is unrolled from the roll, it can be stably unrolled.
[0174] The above-mentioned concavo-convex structure is formed by including a woven fabric in the solid polymer electrolyte membrane. For example, by adjusting the film thickness of the solid polymer electrolyte membrane, the height of the convex parts of the concavo-convex structure can be adjusted.
[0175] In addition, as a method of laminating a woven fabric on a precursor film of a solid polymer electrolyte membrane when manufacturing a solid polymer electrolyte membrane, flat plate pressing and hot roller pressing can be listed. In the case of continuous lamination by hot roller pressing, in order to stably carry out the transportation of the woven fabric and the precursor film, a back tension is sometimes applied to their withdrawal. At this time, if a back tension is applied to the woven fabric, the back tension acts on the filaments extending along the MD (Machine Direction), so the filaments extending along the MD are lifted up. In addition, compared with the case where no back tension is applied, the filaments extending along the TD (Traverse Direction) are deformed more three-dimensionally. If the precursor film is laminated with the woven fabric in this state, the shape of the filaments extending along the TD that have been deformed more three-dimensionally is maintained. In other words, by adjusting the back tension during hot roller pressing, the height of the convex part of the concave-convex structure can also be adjusted.
[0176] When the fabric included in the solid polymer electrolyte membrane is composed of a wire A extending in one direction and a wire B extending in a direction approximately orthogonal to the wire A, the maximum film thickness TA and the minimum film thickness TB of the solid polymer electrolyte membrane are measured for the cross sections of 10 different parts when the solid polymer electrolyte membrane is cut in a direction parallel to the extension direction of the wire A in the solid polymer electrolyte membrane and at the midpoint between the wires A. Furthermore, the maximum film thickness TA and the minimum film thickness TB of the solid polymer electrolyte membrane are measured for the cross sections of 10 different parts when the solid polymer electrolyte membrane is cut in a direction parallel to the extension direction of the wire B in the solid polymer electrolyte membrane and at the midpoint between the wires B. The average minimum film thickness obtained by arithmetic averaging the obtained 20 TBs is set as TB. AVE The average maximum film thickness obtained by arithmetic averaging the 20 TAs is set as TA AVE When the average maximum film thickness TA AVE and the average minimum film thickness TB AVE It is preferable that the relationship of the following formula (X) is satisfied.
[0177] Formula (X) 0.5μm≤(TAAVE -TB AVE ) / 2
[0178] In other words, the average maximum film thickness TA AVE and the average minimum film thickness TB AVE The difference (TA AVE -TB AVE ) is half the value ((TA AVE -TB AVE ) / 2) is preferably 0.5 μm or more.
[0179] By making the above (TA AVE -TB AVE ) / 2 is 0.5 μm or more, the adhesion between the release layer and the solid polymer electrolyte membrane is more excellent, or the unwinding property from the roll obtained by winding the laminate is more excellent.
[0180] Among them, the above (TA AVE -TB AVE The value of ) / 2 is more preferably 1.0 μm or more, further preferably 2.0 μm or more, further preferably 3.0 μm or more, particularly preferably 5.0 μm or more, and most preferably 10.0 μm or more. AVE -TB AVE The upper limit of the value of ) / 2 is not particularly limited, but is often 30.0 μm or less, and more often 20.0 μm or less.
[0181] Below, for the above (TA AVE -TB AVE ) / 2 is calculated using the attached figure.
[0182] Figure 3 The cross-sectional view is a cross-sectional view showing an example of a solid polymer electrolyte membrane included in the laminate of the present invention cut along a direction parallel to the extending direction of the yarn A, specifically, using the method described later. Figure 5 The cross section exposed when the solid polymer electrolyte membrane is cut along the A-A' line. Figure 3 In the cross section of the solid polymer electrolyte membrane 14, the electrolyte 20 containing the fluorinated polymer (I) and the yarns 22a, 22b and 22c disposed in the electrolyte 20 are exposed. The yarns 22a, 22b and 22c correspond to the yarns B constituting the woven fabric 22.
[0183] Figure 4 The cross-sectional view is a cross-sectional view showing an example of a solid polymer electrolyte membrane included in the laminate of the present invention cut along a direction parallel to the extending direction of the filament B, specifically, using the method described later. Figure 5 The cross section exposed when the solid polymer electrolyte membrane is cut along the BB' line. Figure 4 In the cross section of the solid polymer electrolyte membrane 14, the electrolyte 20 containing the fluorinated polymer (I) and the yarns 22A, 22B, and 22C disposed in the electrolyte 20 are exposed. The yarns 22A, 22B, and 22C correspond to the yarns A constituting the woven fabric 22.
[0184] Figure 5 2 is a schematic plan view of the woven fabric 22 in the solid polymer electrolyte membrane 14 when viewed in the membrane thickness direction. Figure 5 As shown, the woven fabric 22 includes the yarns 22A, 22B, and 22C as the yarns A, and the yarns 22a, 22b, and 22c as the yarns B substantially orthogonal to the yarns A.
[0185] First, the maximum film thickness TA and the minimum film thickness TB of the solid polymer electrolyte membrane were measured at 10 different cross sections when the solid polymer electrolyte membrane was cut in a direction parallel to the extension direction of the filaments A in the solid polymer electrolyte membrane and at the midpoint between the filaments A.
[0186] Specifically, in Figure 5 In the example of FIG. 1 , the solid polymer electrolyte membrane 14 is cut using the line AA′ located at the middle point between the wire 22A and the wire 22B as the wire A. Thus, the solid polymer electrolyte membrane 14 is exposed. Figure 3 Similarly, the solid polymer electrolyte membrane 14 is cut at a position other than the middle position between the wire 22A and the wire 22B (e.g., the middle position between the wire 22B and the wire 22C) to expose the cross section of the solid polymer electrolyte membrane 14. In this way, after obtaining cross sections at 10 different locations, the maximum film thickness TA and the minimum film thickness TB of each cross section are measured.
[0187] Furthermore, the maximum film thickness TA and the minimum film thickness TB of the solid polymer electrolyte membrane were measured at 10 different cross sections when the solid polymer electrolyte membrane was cut in a direction parallel to the extension direction of the filaments B in the solid polymer electrolyte membrane and at the midpoint between the filaments B.
[0188] Specifically, in Figure 5 In the example of FIG. 1 , the solid polymer electrolyte membrane 14 is cut using the BB' line located at the middle point between the wire 22a and the wire 22b as the wire B. Thus, the solid polymer electrolyte membrane 14 is exposed. Figure 4 Similarly, the solid polymer electrolyte membrane 14 is cut at a position other than the middle position between the wire 22a and the wire 22b (e.g., the middle position between the wire 22b and the wire 22c) to expose the cross section of the solid polymer electrolyte membrane 14. In this way, after obtaining cross sections at 10 different locations, the maximum film thickness TA and the minimum film thickness TB of each cross section are measured.
[0189] Next, the average maximum film thickness TA obtained by arithmetic averaging the 20 TAs obtained was calculated. AVE The average minimum film thickness TB is obtained by arithmetically averaging the 20 TBs obtained. AVE , find the average maximum film thickness TA AVE and the average minimum film thickness TB AVE The difference between the two values is then divided by 2 to give (TA AVE -TB AVE ) / 2.
[0190] As an adjustment to the above (TA AVE -TB AVE ) / 2, is not limited thereto, and may include: when manufacturing a solid polymer electrolyte membrane, a method of clamping a precursor membrane of the solid polymer electrolyte membrane using a low melting point film described later and heating and pressurizing it. As a result, the low melting point film deforms in a manner that follows the surface shape of the precursor membrane, thereby obtaining a solid polymer electrolyte membrane having a concave-convex structure on the surface, wherein the portion where the silk A and silk B constituting the woven fabric exist is a convex portion, and the portion where the silk A and silk B do not exist is a concave portion.
[0191] In addition, as described above, by adjusting the back tension when the hot roller is pressed, the height of the convex part of the concavo-convex structure can be adjusted, and (TA AVE -TB AVE ) / 2.
[0192] Here, in the measurement of the film thickness of the solid polymer electrolyte membrane, a sample was used in which the solid polymer electrolyte membrane was peeled off from the laminate and dried at 90° C. for 2 hours.
[0193] The maximum film thickness TA and the minimum film thickness TB are measured using an enlarged image (eg, 100 times) of a cross section of the solid polymer electrolyte membrane captured by an optical microscope (product name "BX-51", manufactured by Olympus Corporation).
[0194] From the viewpoint of being able to further reduce the electrolysis voltage when the solid polymer electrolyte membrane is applied to the membrane electrode assembly, the average maximum membrane thickness TA of the solid polymer electrolyte membrane AVE The thickness is preferably 60 to 250 μm, more preferably 60 to 200 μm, further preferably 60 to 140 μm, particularly preferably 60 to 120 μm, and most preferably 60 to 100 μm.
[0195] From the viewpoint of further improving the strength of the membrane electrode assembly including the solid polymer electrolyte membrane, the average minimum film thickness TB of the solid polymer electrolyte membrane AVEIt is preferably 30 to 220 μm, more preferably 30 to 200 μm, further preferably 30 to 130 μm, particularly preferably 30 to 100 μm, particularly preferably 30 to 80 μm, and particularly preferably 30 to 70 μm.
[0196] (Method for producing solid polymer electrolyte membrane)
[0197] As a method for manufacturing a solid polymer electrolyte membrane, the following method can be listed: manufacturing a membrane comprising a precursor membrane and a woven fabric (hereinafter also referred to as "precursor membrane (I')"), wherein the precursor membrane comprises a polymer (hereinafter also referred to as "fluorinated polymer (I')") of a fluorinated monomer (hereinafter also referred to as fluorinated monomer (I')) having a group that can be converted into an ion exchange group, and then converting the group that can be converted into an ion exchange group in the precursor membrane (I') into an ion exchange group for manufacturing.
[0198] Here, a preferred method for producing the precursor film (I') includes a method of sandwiching both surfaces of a laminate having the fluorinated polymer (I') disposed on both surfaces of a woven fabric with a transfer substrate such as a low melting point film having a melting point of 70 to 180°C, followed by heating and pressing.
[0199] Specific examples of the low melting point film include a polyethylene film, a polypropylene film, and a polystyrene film.
[0200] The form of the woven fabric is as described above.
[0201] The fluorinated polymer (I') is preferably a polymer (hereinafter also referred to as "fluorinated monomer (S')") of a fluorinated monomer having a group that can be converted into a sulfonic acid type functional group, and is particularly preferably a fluorinated polymer (S') obtained by copolymerizing a fluorinated olefin with a monomer having a group that can be converted into a sulfonic acid type functional group and a fluorine atom.
[0202] The fluorinated polymer (S') will be described in detail below.
[0203] As the copolymerization method of the fluorinated polymer (S'), known methods such as solution polymerization, suspension polymerization and emulsion polymerization can be adopted.
[0204] Examples of the fluorinated olefin include those exemplified above, and TFE is preferred from the viewpoint of the production cost of the monomer, the reactivity with other monomers, and the excellent properties of the fluorinated polymer (S) to be obtained.
[0205] The fluorinated olefins may be used alone or in combination of two or more.
[0206] Examples of the fluorine-containing monomer (S′) include compounds having one or more fluorine atoms in the molecule, having an ethylenic double bond, and having a group that can be converted into a sulfonic acid type functional group.
[0207] The fluorinated monomer (S') is preferably a compound represented by the formula (2) from the viewpoint of the production cost of the monomer, the reactivity with other monomers, and the excellent properties of the obtainable fluorinated polymer (S).
[0208] Formula (2) CF2=CF-L-(A) n
[0209] L and n in formula (2) are as defined above.
[0210] A is a group that can be converted into a sulfonic acid type functional group. The group that can be converted into a sulfonic acid type functional group is preferably a functional group that can be converted into a sulfonic acid type functional group by hydrolysis. Specific examples of the group that can be converted into a sulfonic acid type functional group include -SO2F, -SO2Cl, and -SO2Br.
[0211] The compound represented by formula (2) is preferably a compound represented by formula (2-1), a compound represented by formula (2-2), a compound represented by formula (2-3), or a compound represented by formula (2-4).
[0212] Formula (2-1) CF2=CF-OR f1 -A
[0213] Formula (2-2) CF2=CF-R f1 -A
[0214]
[0215] R in the formula f1 , R f2 , r and A are defined as above.
[0216]
[0217] R in the formula f1 , R f2 , R f3 , r, m and A are defined as above.
[0218] As the compound represented by the formula (2-1) and the compound represented by the formula (2-1), the compound represented by the formula (2-5) is preferred.
[0219] Formula (2-5) CF2 = CF-(CF2) x -(OCF2CFY) y -O-(CF2) z -SO2F
[0220] In the formula, x, y, z and Y are as defined above.
[0221] Specific examples of the compound represented by formula (2-1) include the following compounds: wherein w is an integer of 1 to 8, and x is an integer of 1 to 5.
[0222] CF2=CF-O-(CF2) w -SO2F
[0223] CF2=CF-O-CF2CF(CF3)-O-(CF2) w -SO2F
[0224] CF2=CF-[O-CF2CF(CF3)] x -SO2F
[0225] Specific examples of the compound represented by formula (2-2) include the following compounds: wherein w in the formula is an integer of 1 to 8.
[0226] CF2=CF-(CF2) w -SO2F
[0227] CF2=CF-CF2-O-(CF2) w -SO2F
[0228] The compound represented by the formula (2-3) is preferably a compound represented by the formula (2-3-1).
[0229]
[0230] R in the formula f4 , R f5 , r and A are defined as above.
[0231] Specific examples of the compound represented by formula (2-3-1) include the following.
[0232]
[0233] The compound represented by the formula (2-4) is preferably a compound represented by the formula (2-4-1).
[0234]
[0235] R in the formula f1 , R f2 and A are defined as above.
[0236] Specific examples of the compound represented by formula (2-4-1) include the following.
[0237]
[0238] The fluorinated monomer (S') may be used alone or in combination of two or more.
[0239] In the production of the fluorinated polymer (S'), other monomers may be used in addition to the fluorinated olefin and the fluorinated monomer (S'). Examples of the other monomers include the monomers exemplified above.
[0240] The ion exchange capacity of the fluorinated polymer (I') can be adjusted by changing the content of the group convertible into an ion exchange group in the fluorinated polymer (I').
[0241] As a specific example of the method for producing the precursor film, an extrusion method can be cited. More specifically, the following method can be cited: forming a film (I') containing a fluorinated polymer (I'), then arranging the film (I'), the woven fabric, and the film (I') in this order, and laminating them using a laminating roll or a vacuum laminating device.
[0242] Specific examples of the method for converting the groups in the precursor film that can be converted into ion exchange groups into ion exchange groups include a method of subjecting the precursor film to a treatment such as a hydrolysis treatment or an acidification treatment.
[0243] Among them, a method of bringing the precursor film into contact with an alkaline aqueous solution is preferred.
[0244] Specific examples of the method of bringing the precursor film into contact with the alkaline aqueous solution include a method of immersing the precursor film in the alkaline aqueous solution and a method of spraying the alkaline aqueous solution onto the surface of the precursor film.
[0245] The temperature of the alkaline aqueous solution is preferably 30 to 100° C., more preferably 40 to 100° C. The contact time between the precursor film and the alkaline aqueous solution is preferably 3 to 150 minutes, more preferably 5 to 50 minutes.
[0246] The alkaline aqueous solution preferably contains an alkali metal hydroxide, a water-soluble organic solvent and water.
[0247] Examples of the alkali metal hydroxide include sodium hydroxide and potassium hydroxide.
[0248] In this specification, the water-soluble organic solvent refers to an organic solvent that is easily soluble in water, and specifically, preferably an organic solvent having a solubility of 0.1 g or more in 1000 ml (20° C.) of water, and more preferably an organic solvent having a solubility of 0.5 g or more. The water-soluble organic solvent preferably includes at least one selected from the group consisting of aprotic organic solvents, alcohols, and amino alcohols, and more preferably includes an aprotic organic solvent.
[0249] The water-soluble organic solvent may be used alone or in combination of two or more.
[0250] Specific examples of the aprotic organic solvent include dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N-ethyl-2-pyrrolidone, and dimethyl sulfoxide is preferred.
[0251] Specific examples of the alcohols include methanol, ethanol, isopropanol, butanol, methoxyethoxyethanol, butoxyethanol, butyl carbitol, hexyloxyethanol, octanol, 1-methoxy-2-propanol, and ethylene glycol.
[0252] Specific examples of amino alcohols include ethanolamine, N-methylethanolamine, N-ethylethanolamine, 1-amino-2-propanol, 1-amino-3-propanol, 2-aminoethoxyethanol, 2-aminothioethoxyethanol, and 2-amino-2-methyl-1-propanol.
[0253] The concentration of the alkali metal hydroxide in the alkaline aqueous solution is preferably 1 to 60% by mass, more preferably 3 to 55% by mass.
[0254] The content of the water-soluble organic solvent in the alkaline aqueous solution is preferably 1 to 60% by mass, more preferably 3 to 55% by mass.
[0255] The concentration of water in the alkaline aqueous solution is preferably 39 to 80% by mass.
[0256] After the precursor film is brought into contact with the alkaline aqueous solution, a treatment for removing the alkaline aqueous solution may be performed. Examples of the method for removing the alkaline aqueous solution include a method of washing the precursor film that has been brought into contact with the alkaline aqueous solution with water.
[0257] After the precursor film is contacted with the alkaline aqueous solution, the resulting film may be contacted with an acidic aqueous solution to convert the ion exchange groups to the acid form.
[0258] Specific examples of the method of bringing the precursor film into contact with the acidic aqueous solution include a method of immersing the precursor film in the acidic aqueous solution and a method of spraying the acidic aqueous solution on the surface of the precursor film.
[0259] The acidic aqueous solution preferably contains an acid component and water.
[0260] Specific examples of the acid component include hydrochloric acid and sulfuric acid.
[0261] [Method for producing laminated body]
[0262] As a method for producing the laminate, for example, the following method can be cited: the releasable substrate and the solid polymer electrolyte membrane are thermally pressed together in a manner such that the solid polymer electrolyte membrane faces the release layer side of the releasable substrate. The thermal pressing can be performed by a roll-to-roll method using a hot roller to apply pressure.
[0263] The temperature of the rollers during the thermocompression bonding using hot rollers is preferably 60 to 200°C, more preferably 90 to 170°C.
[0264] [volume]
[0265] The laminate of the present invention is wound to obtain a roll, which is easy to handle such as transport.
[0266] When the laminate is wound, the laminate may be wound around a winding core as necessary.
[0267] [use]
[0268] The laminate of the present invention can be used for various purposes. For example, it can be used to form a membrane electrode assembly. More specifically, a catalyst layer can be formed on the solid polymer electrolyte membrane in the laminate, and a catalyst layer can be further formed on the surface of the solid polymer electrolyte membrane exposed by peeling off the peelable substrate to form a membrane electrode assembly.
[0269] The catalyst layer can be produced by applying a catalyst layer-forming coating liquid to a predetermined position and drying it as needed. The catalyst layer-forming coating liquid is a liquid obtained by dispersing a polymer having an ion exchange group and a catalyst in a dispersion medium.
[0270] The obtained membrane electrode assembly can be used in a water electrolysis device (specifically, a solid polymer water electrolysis device). In addition, the membrane electrode assembly can be used as a diaphragm of an electrolytic hydrogenation device for aromatic compounds (such as toluene).
[0271] Example
[0272] Hereinafter, the present invention will be described in detail with reference to examples. Examples 1 to 10 are embodiments, and Example 11 is a comparative example. However, the present invention is not limited to these examples.
[0273] [film thickness]
[0274] The average maximum film thickness TA of the solid polymer electrolyte membrane AVE , average minimum film thickness TB AVE and(TA AVE -TB AVE ) / 2 is calculated according to the method described in the column of description of the above-mentioned solid polymer electrolyte membrane.
[0275] [Ion exchange capacity of fluorinated polymer]
[0276] The fluoropolymer was placed in a glove box with dry nitrogen for 24 hours, and the dry mass of the fluoropolymer was measured. Thereafter, the fluoropolymer was immersed in a 2 mol / L sodium chloride aqueous solution at 60°C for 1 hour. After the fluoropolymer was washed with ultrapure water, it was taken out and the liquid immersed in the fluoropolymer was titrated with a 0.1 mol / L sodium hydroxide aqueous solution to obtain the ion exchange capacity (milliequivalent / g dry resin) of the fluoropolymer.
[0277] [Weight per unit area of woven fabric]
[0278] The woven fabric was cut into a size of 20 x 20 cm and its mass was measured. The above measurement was performed 5 times and the average weight (g / m2) was calculated. 2 ).
[0279] [The density of the warp and weft yarns that make up the fabric]
[0280] The density of the warp and weft yarns constituting the woven fabric was calculated as follows: The length of each warp and weft yarn consisting of 10 yarns was measured five times based on the images observed with an optical microscope, and the average value was converted into density (yarns / inch) for calculation.
[0281] [Opening ratio of fabric]
[0282] The calculation was performed by the method described in the column of description of the above woven fabric using a sample obtained by cutting the woven fabric to a size of 20×20 cm.
[0283] [The denier of the warp and weft yarns that make up the fabric]
[0284] The denier of the warp and weft yarns constituting the woven fabric was calculated as follows: Five opening areas were randomly selected, and the opening ratio was calculated from an image observed with an optical microscope, and the average value was taken as the opening ratio.
[0285] [Adhesion Evaluation]
[0286] The peeling force between the peelable substrate and the solid polymer electrolyte membrane was measured in accordance with JIS Z0237 using a TENSILON universal material testing machine RTF-2430 (manufactured by A&D Co., Ltd.) at a peeling angle of 180 degrees, a peeling speed of 300 mm / min, a test piece width of 25 mm, and a test piece length of 50 mm, at a temperature of 23° C. and a relative humidity of 50%. The measured peeling force was evaluated according to the following criteria.
[0287] "0": Peel force is 0.1~3N / 25mm
[0288] “△”: Peel force exceeds 3N / 25mm
[0289] “×”: Peel force is less than 0.1N / 25mm
[0290] In addition, the peeling force is preferably 0.1 N / 25 mm or more from the viewpoint of preventing the solid polymer electrolyte membrane from being easily peeled off from the peelable substrate.
[0291] If the peeling force is too strong, the risk of local breakage of the solid polymer electrolyte membrane increasing when the releasable substrate and the solid polymer electrolyte membrane are separated is increased, so it is preferably 3 N / 25 mm or less.
[0292] [Evaluation of roll-out performance]
[0293] 0.6 m of the laminate obtained in each example with a width of 280 mm was wound on a cylindrical ABS core (manufactured by Showa Maru Co., Ltd., with an outer diameter of 88.5 mm, an inner diameter of 76.5 mm, and a width of 300 mm), and then one end of a biaxially stretched polyester film (manufactured by DuPont Teijin Films, Melinex (registered trademark), with a thickness of 0.1 mm and a width of 280 mm) was connected to one end of the wound laminate, and then the biaxially stretched polyester film was further wound to obtain a roll wound with 100 m. In other words, by winding the biaxially stretched polyester film, the winding of a laminate with a total length of 100 m was simulated. The connection between one end of the laminate and one end of the biaxially stretched polyethylene film was carried out using a heat-resistant polyimide tape (manufactured by 3M JAPAN, 5412, with a width of 19 mm). The winding tension was based on 30 N / full width. After the obtained roll was hung and stored for 1 month, the biaxially stretched polyester film was unwound from the roll, and when the laminate was unwound, the unwinding property was evaluated according to the following criteria.
[0294] “◯”: The solid polymer electrolyte membrane and the releasable substrate were not peeled off and could be rolled out.
[0295] “×”: The solid polymer electrolyte membrane was partially peeled off from the peelable substrate and could not be stably rolled out.
[0296] It should be noted that, as described later, when the laminate is wound on an ABS core, two types of samples are prepared, one in which the solid polymer electrolyte membrane in the laminate is rolled on the outside in a manner closer to the outside than the peelable substrate, and the other in which the solid polymer electrolyte membrane in the laminate is rolled on the inside in a manner closer to the inside than the peelable substrate, and the above-mentioned evaluation is carried out.
[0297] [Production of fluorinated polymer (S'-1)]
[0298] CF2=CF2 was copolymerized with a monomer (Y) represented by the following formula (Y) to obtain a fluorinated polymer (S'-1) (ion exchange capacity: 1.25 meq / g dry resin).
[0299] CF2=CF-O-CF2CF(CF3)-O-CF2CF2-SO2F···(Y)
[0300] [Production of fluorinated polymer (S'-2)]
[0301] CF2=CF2 is copolymerized with the monomer (Y) represented by the above formula (Y) to obtain a fluorinated polymer (S'-2) (ion exchange capacity: 1.00 meq / g dry resin).
[0302] The ion exchange capacity described in the above [Production of Fluoropolymer (S'-1)] means the ion exchange capacity of a fluorinated polymer obtained by hydrolyzing the fluorinated polymer (S'-1) according to the procedure described later.
[0303] Similarly, the ion exchange capacity described in [Production of Fluoropolymer (S'-2)] means the ion exchange capacity of a fluorinated polymer obtained when the fluorinated polymer (S'-2) is hydrolyzed in the step described later.
[0304] [Manufacturing of Thin Film-Attached Substrate Y1]
[0305] The fluorinated polymer (S'-1) is attached to a substrate formed of a linear low-density polyethylene (LLDPE) film (melting point: 110-120°C, thickness: 0.1 mm) by a melt extrusion method to obtain a substrate Y1 with a film having a film α1 (film thickness: 30 μm) formed on the substrate and formed thereon.
[0306] [Manufacturing of substrate Y2 with thin film]
[0307] The fluorinated polymer (S'-1) is attached to a substrate formed of a biaxially stretched polyester film (manufactured by DuPont Teijin Films, Melinex (registered trademark), thickness: 0.1 mm, width: 400 mm) by a melt extrusion method to obtain a substrate Y2 with a film having a film α2 (film thickness: 60 μm) formed on the substrate and formed thereon.
[0308] [Manufacturing of thin film-attached substrate Y3]
[0309] The fluorinated polymer (S'-2) is attached to a substrate formed of a biaxially stretched polyester film (manufactured by DuPont Teijin Films, Melinex (registered trademark), thickness: 0.1 mm, width: 400 mm) by a melt extrusion method to obtain a substrate Y3 with a film having a film α3 (film thickness: 60 μm) formed on the substrate and formed thereon.
[0310] [Manufacturing of thin film-coated substrate Y4]
[0311] The fluorinated polymer (S'-2) is attached to a substrate formed of a biaxially stretched polyester film (manufactured by DuPont Teijin Films, Melinex (registered trademark), thickness: 0.1 mm, width: 400 mm) by a melt extrusion method to obtain a substrate Y4 with a film having a film α4 (film thickness: 80 μm) formed on the substrate and formed thereon.
[0312] [Manufacturing of substrate Y5 with thin film]
[0313] The fluorinated polymer (S'-2) is attached to a substrate formed of a biaxially stretched polyester film (manufactured by DuPont Teijin Films, Melinex (registered trademark), thickness: 0.1 mm, width: 400 mm) by a melt extrusion method to obtain a substrate Y5 with a film having a film α5 (film thickness: 115 μm) formed on the substrate and formed thereon.
[0314] [Manufacturing of thin film-coated substrate Y6]
[0315] The fluorinated polymer (S'-1) is attached to a substrate formed of a biaxially stretched polyester film (manufactured by DuPont Teijin Films, Melinex (registered trademark), thickness: 0.1 mm, width: 400 mm) by a melt extrusion method to obtain a substrate Y6 with a film having a film α6 (film thickness: 130 μm) formed on the substrate and formed thereon.
[0316] [Manufacture of woven fabrics]
[0317] PFA yarns with a denier of 18.6 were used as warp yarns and weft yarns, and the yarns were plain woven so that the density of the PFA yarns was 100 yarns / inch to obtain woven fabric A1. The weight per unit area of woven fabric A1 was 16.3 g / m 2 The opening ratio of fabric A1 is 74.3%.
[0318] It should be noted that the warp and weft threads are composed of slit film threads.
[0319] It should be noted that the yarn A and the yarn B are composed of monofilaments.
[0320] Woven cloth A2 was produced in the same manner as woven cloth A1 except that the types and deniers of the materials constituting the warp and weft, and the density, basis weight, and opening ratio of the woven cloth were changed so as to be the values described in Table 1.
[0321] [Manufacturing of the peelable substrate 1]
[0322] A main agent: LX-75A (manufactured by DIC GRAPHICS), a curing agent: KW-75 (manufactured by DIC GRAPHICS), and a diluent: ethyl acetate were mixed in the proportion of 60 parts by mass / 10 parts by mass / 60 parts by mass to prepare an adhesive.
[0323] Next, on a biaxially stretched polyester film (Melinex (registered trademark), manufactured by DuPont Teijin Films, thickness: 50 μm, elastic modulus at 160° C.: 40 MPa) as a support, a 2 g / m 2 The above adhesive is applied in a manner.
[0324] On the adhesive layer formed by evaporating the solvent of the adhesive in a drying furnace, an LDPE film (AJ-1 manufactured by TAMAPOLY, thickness: 50 μm, elastic modulus at 160° C.: 0 MPa) was laminated by a dry laminator to form a release layer, thereby manufacturing a releasable substrate 1. At this time, the corona-treated surface side of the LDPE film was set to be attached to the adhesive layer formed on the support.
[0325] [Manufacturing of the peelable substrate 2]
[0326] Releasable substrate 2 was produced in the same manner as that of releasable substrate 1 using LLDPE (low-density polyethylene film (Tamapolly, M-6), thickness: 100 μm, elastic modulus at 160° C.: 0 MPa) instead of LDPE film (Tamapolly, AJ-1).
[0327] [Manufacturing of the peelable substrate 3]
[0328] On the surface of the support body in the peelable substrate 2 where the release layer is not laminated, ETFE (tetrafluoroethylene-ethylene copolymer, single-sided pear-ground film (AGC, 50HK), thickness: 50 μm, elastic modulus at 160° C.: 48 MPa) was used to manufacture the peelable substrate 3 in which ETFE and the peelable substrate 2 were laminated via an adhesive layer in the same steps as the manufacturing steps of the peelable substrate 1. At this time, the mirror-surface and corona-treated surface side of the ETFE film was set to be attached to the adhesive layer formed on the support body.
[0329] [Manufacturing of the peelable substrate 4]
[0330] A biaxially stretched polyester film (Melinex (registered trademark), manufactured by DuPont Teijin Films, thickness: 188 μm, elastic modulus at 160° C.: 40 MPa) was used as a support, LLDPE (low-density polyethylene film (M-6 manufactured by TAMAPOLY Co., Ltd.), thickness: 60 μm, elastic modulus at 160° C.: 0 MPa) was used as a release layer, and ETFE (tetrafluoroethylene-ethylene copolymer, single-sided pear film (30HK manufactured by AGC Co., Ltd.), thickness: 30 μm, elastic modulus at 160° C.: 48 MPa) was used as a roll-out improvement layer on the surface of the support on which the release layer was not laminated. After lamination via an adhesive layer in the same procedure as the production procedure of the release substrate 1, the LLDPE surface of the release layer was subjected to a 42 dyne corona treatment to produce a release substrate 4. At this time, the mirror surface and corona-treated surface side of the ETFE film was set to be attached to the adhesive layer formed on the support.
[0331] [Example 1]
[0332] The substrate with film Y1 / woven fabric A1 / substrate with film Y1 were stacked in this order. The substrate with film Y1 was arranged so that the film α1 in the substrate with film Y1 was in contact with the woven fabric A1.
[0333] Utilization temperature: 160°C, surface pressure: 30MPa / m 2 The stacked members were heat-pressed for 10 minutes using a flat plate press, and then the substrates on both sides were peeled off at a temperature of 50° C. to obtain a precursor film.
[0334] The precursor film was immersed in a solution of dimethyl sulfoxide / potassium hydroxide / water = 30 / 5.5 / 64.5 (mass ratio) at 95°C for 30 minutes, and the groups in the precursor film that can be converted into sulfonic acid-type functional groups were hydrolyzed and converted into K-type sulfonic acid-type functional groups, and then washed with water. Thereafter, the obtained film was immersed in 1M sulfuric acid, and the terminal groups were converted from K-type to H-type, and then dried to obtain a solid polymer electrolyte membrane 1.
[0335] The average maximum film thickness TA of the solid polymer electrolyte membrane 1 AVE The average minimum film thickness TB is 91μm. AVE 60μm, (TA AVE -TB AVE ) / 2 is 15.5μm.
[0336] Next, the prepared release substrate 1 and the solid polymer electrolyte membrane 1 are introduced between a metal roller and a rubber roller using a hot roll press device and thermocompressed to thereby join them to obtain a laminate 1. At this time, in the laminate 1 obtained as a transport film, the support, the release layer and the solid polymer electrolyte membrane 1 are sequentially laminated.
[0337] The surface pressure of the rubber roller in pressure contact with the metal roller was 200 N / cm, the temperature of the metal roller and the rubber roller was 160° C., and the conveying speed was 10 cm / min.
[0338] [Example 2]
[0339] A laminate 2 was obtained by following the same procedure as in Example 1 except that the release substrate 2 was used instead of the release substrate 1.
[0340] [Example 3]
[0341] A laminate 3 was obtained by following the same procedure as in Example 1 except that the release substrate 3 was used instead of the release substrate 1 .
[0342] [Example 4]
[0343] A laminate 4 was obtained by the same procedure as in Example 1 except that the releasable substrate 3 was used instead of the releasable substrate 1 and the woven fabric A2 was used instead of the woven fabric A1.
[0344] [Example 5]
[0345] A laminate 5 was obtained by following the same procedure as in Example 1 except that the substrate with a film Y2 was used instead of the substrate with a film Y1 and the release substrate 3 was used instead of the release substrate 1 .
[0346] [Example 6]
[0347] A laminate 6 was obtained by the same procedure as in Example 1 except that the substrate with a film Y2 was used instead of the substrate with a film Y1, the releasable substrate 3 was used instead of the releasable substrate 1, and the woven fabric A2 was used instead of the woven fabric A1.
[0348] [Example 7]
[0349] A laminate 7 was obtained by following the same procedure as in Example 1 except that the substrate with a film Y3 was used instead of the substrate with a film Y1 and the release substrate 3 was used instead of the release substrate 1 .
[0350] [Example 8]
[0351] A laminate 8 was obtained by the same procedure as in Example 1 except that the substrate with a film Y4 was used instead of the substrate with a film Y1, the releasable substrate 3 was used instead of the releasable substrate 1, and the woven fabric A2 was used instead of the woven fabric A1.
[0352] [Example 9]
[0353] A laminate 9 was obtained by the same procedure as in Example 1 except that the substrate with a film Y5 was used instead of the substrate with a film Y1, the releasable substrate 3 was used instead of the releasable substrate 1, and the woven fabric A2 was used instead of the woven fabric A1.
[0354] [Example 10]
[0355] A laminate 10 is obtained by following the same steps as in Example 1 except that a substrate Y2 with a film is used instead of the substrate Y1 with a film, a peelable substrate 4 is used instead of the peelable substrate 1, the temperature of the metal roller of the hot roller press device is set to 130°C, and the temperature of the rubber roller is set to 90°C.
[0356] [Example 11]
[0357] A thin film obtained by peeling off a substrate from a substrate Y6 with a thin film is used as a precursor film to manufacture a solid polymer electrolyte membrane 10. The solid polymer electrolyte membrane 10 is used to replace the solid polymer electrolyte membrane 1, and the peelable substrate 3 is used to replace the peelable substrate 1. Except for this, the same steps as Example 1 are followed to obtain a laminate 10.
[0358] The solid polymer electrolyte membrane 10 in the laminate 10 does not contain woven fabric.
[0359] The column "Total film thickness (μm) of thin films" in Table 1 means the total film thickness of thin films in the substrate with thin films used in each example. For example, in Example 1, two substrates Y1 with thin films were used, so the total value of two 30μm thin films, i.e., 60μm, is shown in Table 1.
[0360] The “Presence / Absence” column in the “Fabric” column in Table 1 indicates whether the solid polymer electrolyte membrane includes fabric. “Presence” indicates that the fabric is included, and “Absence” indicates that the fabric is not included.
[0361] The "Type" column in the "Releasable Base Material" column in Table 1 shows the type of the releasable base material used in each example, and "1" to "4" respectively represent releasable base materials 1 to 4.
[0362] In addition, in Example 11, the evaluation of roll-out property was "×", and thus the evaluation of adhesion was not performed, and thus "-" was indicated.
[0363] [Table 1]
[0364]
[0365] As shown in Table 1, it was confirmed that the laminated body of the present invention exhibited the desired effects.
[0366] It should be noted that the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2022-115790 filed on July 20, 2022 are incorporated herein as the disclosed contents of the specification of the present invention.
[0367] Description of Reference Numerals
[0368] 10-layer stack
[0369] 12Releasable substrate
[0370] 14Solid polymer electrolyte membrane
[0371] 16 Support
[0372] 18 Release layer
[0373] 19 Roll-out improvement layer
[0374] 20 electrolytes
[0375] 22 Weaving
[0376] 22a, 22b, 22c wire B
[0377] 22A, 22B, 22C wire A
Claims
1. A laminate comprising a peelable substrate and a solid polymer electrolyte membrane, wherein the peelable substrate comprises a support and a release layer, and the solid polymer electrolyte membrane is disposed on the release layer in the peelable substrate, The solid polymer electrolyte membrane comprises a fluorine-containing polymer having ion exchange groups and a woven fabric.
2. The laminate according to claim 1, wherein The ion exchange capacity of the fluorine-containing polymer is 0.90 to 2.00 milliequivalents per gram of dry resin.
3. The laminate according to claim 1 or 2, wherein: The woven fabric is composed of a thread A extending in one direction and a thread B extending in a direction substantially perpendicular to the thread A. The opening ratio of the woven fabric is greater than 50%.
4. The laminate according to claim 3, wherein: The denier of the yarn A and the denier of the yarn B are each independently 15 to 50.
5. The laminate according to claim 3, wherein The yarn A and the yarn B are each independently made of at least one material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyetheretherketone, and polyphenylene sulfide.
6. The laminate according to claim 3, wherein The density of the yarn A and the yarn B is independently 70 to 150 yarns / inch.
7. The laminate according to claim 1 or 2, wherein: The ion exchange group is a sulfonic acid type functional group.
8. The laminate according to claim 1 or 2, wherein: The fluorine-containing polymer includes a fluorine-containing olefin-based unit and a unit having a sulfonic acid-type functional group and a fluorine atom.
9. The laminate according to claim 8, wherein The fluorine-containing olefin is a fluorine olefin having one or more fluorine atoms in the molecule and having 2 to 3 carbon atoms.
10. The laminate according to claim 8, wherein The unit having a sulfonic acid type functional group and a fluorine atom is a unit represented by formula (1), Formula (1) -[CF2-CF(-L-(SO3M) n )]- L is an n+1-valent perfluorocarbon group which may contain an ethereal oxygen atom, M is a hydrogen atom, an alkali metal or a quaternary ammonium cation, and n is 1 or 2.
11. The laminate according to claim 1 or 2, wherein The elastic modulus of the support at 160°C is greater than the elastic modulus of the release layer at 160°C.
12. The laminate according to claim 1 or 2, wherein: The release layer has an elastic modulus of 1 MPa or less at 160°C.
13. The laminate according to claim 1 or 2, wherein: The woven fabric is composed of a thread A extending in one direction and a thread B extending in a direction substantially perpendicular to the thread A. The maximum film thickness TA and the minimum film thickness TB of the solid polymer electrolyte membrane are measured at 10 different cross sections when the solid polymer electrolyte membrane is cut in a direction parallel to the extension direction of the filaments A in the solid polymer electrolyte membrane and at the middle point between the filaments A. Furthermore, the maximum film thickness TA and the minimum film thickness TB of the solid polymer electrolyte membrane were measured at 10 different cross sections when the solid polymer electrolyte membrane was cut in a direction parallel to the extension direction of the filaments B in the solid polymer electrolyte membrane and at the midpoint between the filaments B. The average minimum film thickness obtained by arithmetic averaging the 20 TBs obtained is set as TB. AVE , and the average maximum film thickness obtained by arithmetic averaging the 20 TAs obtained is set as TA AVE When the average maximum film thickness TA AVE and the average minimum film thickness TB AVE Satisfies the following relationship of formula (X), Formula (X) 0.5μm ≤ (TA AVE - TB AVE ) / 2.
14. A roll obtained by winding the laminate according to claim 1 or 2.
Citation Information
Patent Citations
Device for manufacturing fuel battery cell joined body
JP2020107430A
Mass spectroscope
JP2022115790A